Ultrasmall Mode Volumes of Multilayered Hyperbolic Metamaterial Nanocavities in the Visible Range - Song Yang; Jianhua Yang; Xiaokang Song; Yuanqi Huang; Li Yu (IEEE Photonics Journal)
Designing optical nanocavities with high quality factors (Q) or small mode volume (Vm) has important applications in the field of quantum information due to the strong light-matter coupling phenomena. The multilayered hyperbolic metamaterial (HMM) nanocavities have been designed and numerically investigated to achieve the small mode volume. Unique dispersion relations of our HMM nanocavity enable propagation of large wave vectors result in strong wave confinement. The excitation of coupled localized surface plasmons, which have achieved ultrasmall mode volume below 10 –6 λ3 or high Q/Vm around 107 λ–3 causing better electric fields confinement. These properties can be demonstrated by rationally the geometrical parameters and may have potential applications in light-matter interaction.